\(\sqrt{\frac{1}{4}}\)=

b) \(\sqrt{625}\)

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(\sqrt{\frac{1}{9}+\frac{1}{16}}\)

\(=\frac{1}{3}+\frac{1}{4}\)

\(=\frac{7}{12}\)

\(\sqrt{4+36+81}\)

\(=\sqrt{121}\)

\(=\pm11\)

4 tháng 8 2019

a) \(\sqrt{\frac{4}{81}}:\sqrt{\frac{25}{81}}-1\frac{2}{5}\)

\(=\frac{2}{9}:\frac{5}{9}-\frac{7}{5}\)

\(=\frac{2}{5}-\frac{7}{5}\)

\(=-1.\)

b) \(\sqrt{36}.\sqrt{\frac{25}{16}}+\frac{1}{4}\)

\(=6.\frac{5}{4}+\frac{1}{4}\)

\(=\frac{15}{2}+\frac{1}{4}\)

\(=\frac{31}{4}.\)

c) \(1\frac{1}{2}+\frac{4}{7}:\left(-\frac{8}{9}\right)\)

\(=\frac{3}{2}+\frac{4}{7}:\left(-\frac{8}{9}\right)\)

\(=\frac{3}{2}+\left(-\frac{9}{14}\right)\)

\(=\frac{6}{7}.\)

d) \(1,17-0,4.\left(\frac{1}{2}\right)^2-\frac{1}{-5}\)

\(=\frac{117}{100}-\frac{2}{5}.\frac{1}{4}-\left(-\frac{1}{5}\right)\)

\(=\frac{117}{100}-\frac{1}{10}+\frac{1}{5}\)

\(=\frac{107}{100}+\frac{1}{5}\)

\(=\frac{127}{100}.\)

Chúc bạn học tốt!

4 tháng 8 2019

a, \(\frac{4}{81}:\sqrt{\frac{25}{81}-1\frac{2}{5}}\)

\(\Rightarrow\frac{4}{81}:\frac{5}{9}-\frac{7}{5}\)

\(\Rightarrow\frac{4}{81}.\frac{9}{5}-\frac{7}{5}\)

\(\Rightarrow\frac{4}{9}.\frac{1}{5}-\frac{7}{5}\)

\(\Rightarrow\frac{-59}{45}\)

b,\(\sqrt{36}.\sqrt{\frac{25}{16}+\frac{1}{4}}\)

\(\Rightarrow6.\frac{5}{4}+\frac{1}{4}\)

\(\Rightarrow\frac{15}{2}+\frac{1}{4}\)

\(\Rightarrow\frac{31}{4}\)

c,\(1\frac{1}{2}+\frac{4}{7}:\frac{-8}{9}\)

\(\Rightarrow\frac{3}{2}-\frac{4}{7}.\frac{-8}{9}\)

\(\Rightarrow\frac{3}{2}-\frac{9}{14}\)

\(\Rightarrow\frac{6}{7}\)

d, \(1,17-\left(0,4.\frac{1}{2}\right)^2-\frac{1}{5}\)

\(\Rightarrow\frac{117}{100}-\left(\frac{1}{5}\right)^2-\frac{1}{5}\)

\(\Rightarrow\frac{117}{100}-\frac{1}{25}-\frac{1}{5}\)

\(\Rightarrow\frac{93}{100}\)

17 tháng 7 2019

1. a) 3+2=5

b) 0,5-0,1=0,4

c) 4/5-1/9=31/45

d) 2-0,6=1,4

2. a) 8-4+3=7

b) 11+5-3=13

c) 3/2-4/6-7-37/6

d) 4+5-6=3

17 tháng 7 2019

Mơn nhìu <3

25 tháng 11 2019

Bai 1

a) \(\sqrt{0,36}+\sqrt{0,49}=0,6+0,7=1,3\)

b) \(\sqrt{\frac{4}{9}}-\sqrt{\frac{25}{36}}=\frac{2}{3}-\frac{5}{6}\)

=\(-\frac{1}{6}\)

Bài 2

a)\(x^2=81\Rightarrow\left[{}\begin{matrix}x=9\\x=-9\end{matrix}\right.\)

b) \(\left(x-1\right)^2=\frac{9}{16}\)

\(\Rightarrow\left[{}\begin{matrix}x-1=\frac{3}{4}\\x-1=\frac{-3}{4}\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\frac{7}{4}\\x=\frac{1}{4}\end{matrix}\right.\)

c) \(x-2\sqrt{x}=0\Rightarrow\sqrt{x}\left(\sqrt{x}-2\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}\sqrt{x}=0\\\sqrt{x}-2=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=4\end{matrix}\right.\)

d) \(x=\sqrt{x}\Rightarrow x-\sqrt{x}=0\Rightarrow\sqrt{x}\left(\sqrt{x}-1\right)=0\)

\(\Rightarrow\left[{}\begin{matrix}\sqrt{x}=0\\\sqrt{x}-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)

12 tháng 10 2020

a) \(C=3\cdot\sqrt{25}-3\cdot\sqrt{\frac{1}{9}}\)

\(C=3\cdot5-3\cdot\frac{1}{3}\)

\(C=15-1=14\)

b) \(D=-4\sqrt{\frac{4}{25}}+3\sqrt{0,16}-2\sqrt{0,04}\)

\(D=-4\cdot\frac{2}{5}+3\cdot\frac{2}{5}-2\cdot\frac{1}{5}\)

\(D=\frac{1}{5}\cdot\left(-8+6-2\right)\)

\(D=\frac{1}{5}\cdot\left(-4\right)=-\frac{4}{5}\)

\(b,\left(\sqrt{1\frac{9}{16}-\sqrt{\frac{9}{16}}}\right):5\)

\(=\left(\sqrt{\frac{25}{16}-\frac{3}{4}}\right):5\)

\(=\sqrt{\frac{13}{16}}:5\)

\(=\frac{\sqrt{13}}{4}:5\)

\(=\frac{\sqrt{13}}{20}\)

21 tháng 9 2017

a)\(\sqrt{1}\)+\(\sqrt{9}\)+\(\sqrt{25}\)+\(\sqrt{49}\)+\(\sqrt{81}\)

=1+3+5+7+9

=25

b)=\(\dfrac{1}{2}\)+\(\dfrac{1}{3}\)+\(\dfrac{1}{6}\)+\(\dfrac{1}{4}\)

=\(\dfrac{6}{12}\)+\(\dfrac{4}{12}\)+\(\dfrac{2}{12}\)+\(\dfrac{3}{12}\)

=\(\dfrac{15}{12}\)

c) =0,2+0.3+0,4

= 0.9

d) =9-8+7

=8

j) =1,2-1,3+1.4

= (-0,1)+1,4

=1,4

g) \(\dfrac{2}{5}\)+\(\dfrac{5}{2}\)+\(\dfrac{9}{10}\)+\(\dfrac{3}{4}\)

= (\(\dfrac{4}{10}\)+\(\dfrac{15}{10}\)+\(\dfrac{9}{10}\))+\(\dfrac{3}{4}\)

= \(\dfrac{14}{5}\)+\(\dfrac{3}{4}\)

=\(\dfrac{56}{20}\)+\(\dfrac{15}{20}\)

= \(\dfrac{71}{20}\)

Nhớ tick cho mk nha~

26 tháng 7 2019

a)\(\sqrt{0,09}\)+2.\(\sqrt{0,25}\)=0,3+2.0,5

                                            =0,3+1

                                            =1,3      

b)0,5.\(\sqrt{100}\)-\(\sqrt{\frac{4}{25}}\)=0,5.10-0,4

                                           =5-0,4

                                           =4,6

c)(\(\sqrt{1\frac{9}{16}}\)  -\(\sqrt{\frac{9}{16}}\)):5=(1,25-0,75):5

                                              =0,5:5

                                              =0,1

d)3.\(\sqrt{1\frac{17}{64}}\) -2.\(\sqrt{0,0625}\)=1,125-2.0,25

                                                      =1,125-0,5

                                                      =0,625